Conductive structure color powder based on glucose in-situ growth and preparation and application thereof
By growing glucose particles in situ on the surface of the conductive powder microspheres to form conductive structural powder, the problems of uncontrollable color and angle dependence of existing structural color powder are solved, and the effects of uniform color, high saturation and adjustable color are achieved.
Patent Information
- Application Number
- CN202411610902.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-07
AI Technical Summary
The existing structural color toners have problems such as uncontrollable color, low saturation, uneven color distribution or large dependence on the angle of color rendering, resulting in poor color regulation effect.
The conductive structure-colored powder is formed by growing glucose particles in situ on the surface of the conductive powder microspheres. The powder includes conductive powders such as multi-layer graphene, single-walled carbon nanotubes or carbon black. The glucose particles are converted into carbon materials through high-temperature heat treatment to form a stable composite structure.
It realizes a conductive structural color powder with uniform color, high saturation, uniform color distribution and unrestricted angle, and can regulate the color of structural color powder and is suitable for a variety of application scenarios.
Smart Images

Figure CN119570284A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of structural color materials, and in particular to a conductive structural color powder based on in-situ growth of glucose and the preparation and application thereof. Background Art
[0002] Traditional color development technology usually uses pigments to develop colors. However, pigments have disadvantages such as unstable chemical properties, environmental unfriendliness, and easy fading, which limits their application.
[0003] Compared with pigment color, structural color is achieved by regulating light based on the periodic micro-nano structure of the material (such as gratings, photonic crystals, etc.). It has the advantages of stable chemical properties, environmental protection, high resolution, etc., and has broad application prospects in display, sensing and anti-counterfeiting. In particular, the composite periodic micro-nano structure existing in natural organisms can produce better optical effects, such as mixed colors, polarization, ultra-white, ultra-black, dynamic structural colors, etc., which provides ideas for the preparation of new optical materials. However, the current structural color toner has problems such as uncontrollable color, low saturation, uneven color distribution or large angle dependence of color rendering, and the color regulation effect of structural color toner needs to be improved.
[0004] Therefore, it is necessary to provide a technical solution for improving the color control effect of structural color toner. Summary of the invention
[0005] In view of this, the present application provides a conductive structural color powder based on in-situ growth of glucose and its preparation and application, which are used to solve the problem of how to improve the color regulation effect of structural color powder.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a conductive structural color powder based on in-situ growth of glucose, which includes conductive powder and glucose particles in-situ grown on the surface of the conductive powder, wherein the conductive powder includes one or more of multilayer graphene, single-walled carbon nanotubes, and carbon black.
[0007] Preferably, the particle size of the glucose particles on the conductive structural color powder is 260-350 nm.
[0008] Preferably, the conductive structural color powder is a spherical powder with the same particle size.
[0009] In a second aspect, the present application provides a method for preparing a conductive structural color powder based on in-situ growth of glucose, comprising the following steps: S1. The conductive powder is placed in a water solvent for pretreatment, and then dried to obtain a pretreated conductive powder; S2. adding the pretreated conductive powder to the glucose solution, dispersing by ultrasonication, and heating the solution to obtain a composite; S3. Soak the composite in an alkaline solution and then dry it to obtain a conductive structural color powder based on in-situ growth of glucose.
[0010] Preferably, the concentration of the glucose solution is 0.1-20%.
[0011] Preferably, the solvent in step S1 comprises acetone, ethanol and deionized water in a volume ratio of 0.8-1:0.8-1:1.5-2; and the standing time is 24-48 hours.
[0012] Preferably, in step S2, the heating reaction process is: heating to 200-250°C at 2-5°C / min.
[0013] Preferably, in step S3, the concentration of the ammonia water is 25-30%, and the soaking time is 0.5-1h.
[0014] Preferably, in step S3, the drying temperature is 60-90°C.
[0015] In a third aspect, the present application provides an application of a conductive structural color powder based on in-situ growth of glucose in color control.
[0016] The beneficial effects of the present application are as follows: The present application obtains a conductive structural color powder with uniform color, high color saturation, high thermal stability and low color rendering angle dependence by uniformly growing glucose in situ on the surface of conductive powder microspheres. The color of the structural color powder can be controlled by adjusting the amount of raw materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the appearance of powders with different structural colors; Figure 2 The test results of the size of different structural color powders; Figure 3 is the absorbance curve of powders with different structural colors; Figure 4 Schematic diagram of the microstructure of the structural color powder of this application; Figure 5 This is a reflection peak curve diagram of structural color powder at different angles. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] In a first aspect, the present application provides a conductive structural color powder based on in-situ growth of glucose, which includes a conductive powder and glucose particles in-situ grown on the surface of the conductive powder, wherein the conductive powder includes one or more of multilayer graphene, single-walled carbon nanotubes, and carbon black.
[0020] In the present application, glucose particles are in-situ grown on the surface of the conductive powder sphere, and the glucose is evenly distributed and has high stability in combination with the conductive powder, so that the color distribution of the structural color powder is even and the angle dependence is low.
[0021] In the present application, glucose can be converted into a carbon material with good electrical conductivity and optical properties during the heat treatment process, and the combination of glucose and a specific conductive powder can realize the preparation of a conductive structural color powder. Among them, the carbon material formed by glucose during the heat treatment process can form a uniform composite structure with the conductive powder, which helps to achieve color uniformity and saturation. At the same time, due to the optical properties of the carbon material, the prepared powder has good structural color performance, which is usually not limited by the observation angle. At the same time, the carbon layer formed by the decomposition of glucose at high temperature can be evenly coated on the surface of the conductive powder to form a core-shell structure. This core-shell structure not only enhances the conductivity of the powder, but also gives the powder a specific color and gloss due to the optical properties of the carbon layer. The formation of this color has nothing to do with the amount of conductive powder used, and the concentration of glucose plays a decisive role in the formation of color.
[0022] In some embodiments, the glucose particles on the conductive structural color powder have a particle size of 260-350 nm.
[0023] like Figure 4 As shown, the particle size of the glucose particles on the conductive structural color powder affects the color it presents. Within this particle size range, the conductive structural color powder of the present application can present different colors, with high saturation and adjustable colors. The gaps between conductive structural color powders of different particle sizes are different, and the wavelengths of light diffraction are different, so the colors of the conductive powders presented are different. Within the gap range of the present application, the color of the structural color powder is adjustable.
[0024] In some embodiments, the conductive structural color powder is a spherical powder with the same particle size.
[0025] The conductive structural color powder of the present application has the same particle size, which ensures the uniformity of color development and reduces the angle dependence.
[0026] The present application provides a method for preparing a conductive structural color powder based on in-situ growth of glucose, comprising the following steps: S1. The conductive powder is placed in a water solvent for pretreatment, and then dried to obtain a pretreated conductive powder; S2. adding the pretreated conductive powder to the glucose solution, dispersing by ultrasonication, and heating the solution to obtain a composite; S3. Soak the composite in an alkaline solution and then dry it to obtain a conductive structural color powder based on in-situ growth of glucose.
[0027] In the present application, step S1 is a pretreatment step, which is performed by placing the conductive powder in a solution composed of acetone, ethanol and deionized water for pretreatment. Step S1 helps to remove impurities and oil stains on the surface of the conductive powder, thereby improving its surface activity and reactivity. Step S2 is a process of mixing glucose solution with conductive powder. In step S2, glucose can be converted into carbon material at high temperature. This carbon material forms a composite with the conductive powder, which enhances the conductivity and structural color properties of the powder. Among them, ultrasonic dispersion treatment helps to uniformly mix the glucose solution and the conductive powder to form a uniform composite structure. Step S3 is an alkaline solution treatment. The alkaline solution treatment is used to further remove impurities on the surface of the composite, and may also help to improve the surface properties of the powder, enhance its conductivity, improve drying efficiency, and reduce drying time.
[0028] In some embodiments, the alkaline solution of the present application is ammonia water, which is intended to adjust the surface properties of the powder through the alkaline environment of the ammonia water to form or improve the conductive network of the powder; at the same time, since ammonia water is volatile, soaking in an ammonia solution can improve the drying efficiency, reduce the drying time, improve the surface properties and conductivity of the powder, and remove impurities that may affect the conductive properties (grease and organic matter on the surface of the metal powder).
[0029] The above preparation method can achieve uniform color, high saturation, uniform color distribution and no angle restriction. The effect mechanism is as follows: 1. In-situ growth of glucose: Glucose is converted into carbon material at high temperature, which forms a uniform composite structure with conductive powder, helping to achieve color uniformity and saturation.
[0030] 2. Formation of structural color: Structural color is achieved based on the regulation of light by the periodic micro-nano structure of matter. This type of structural color has the advantages of stable chemical properties, environmental protection, high resolution, and is independent of the observation angle. Therefore, the color distribution is uniform and not restricted by angle.
[0031] 3. High temperature heat treatment: High temperature heat treatment helps to form a stable carbon structure and enhance the thermal stability and structural color properties of the material.
[0032] 4. Post-treatment with ammonia solution: Treatment with ammonia solution may help improve the surface properties of the powder, enhance its conductivity and structural color performance, thereby achieving color uniformity and high saturation.
[0033] The present invention uses glucose in-situ growth and high-temperature heat treatment, combined with ammonia solution post-treatment, to effectively prepare conductive structural color powder with uniform color, high saturation, uniform color distribution and no angle restriction. This preparation method utilizes the characteristics of glucose being converted into carbon materials at high temperatures and the formation mechanism of structural colors to achieve precise control and optimization of color.
[0034] In some embodiments, the concentration of the glucose solution is 0.1-20.
[0035] The carbon layer formed by glucose decomposition at high temperature can be evenly coated on the surface of the conductive powder to form a core-shell structure. This core-shell structure not only enhances the conductivity of the powder, but also gives the powder a specific color and luster due to the optical properties of the carbon layer. The formation of this color has nothing to do with the amount of conductive powder used, but is closely related to the concentration of the glucose solution.
[0036] In the present application, the amount of glucose used affects the particle size of the conductive structural color powder obtained, and further affects the final color type, saturation and purity of the conductive structural color powder.
[0037] In some embodiments, the solvent in step S1 includes acetone, ethanol and deionized water in a volume ratio of 0.8-1:0.8-1:1.5-2; and the standing time is 24-48 hours.
[0038] In some embodiments, in step S2, the heating reaction process is: heating to 200-250°C at 2-5°C / min.
[0039] In some embodiments, in step S3, the concentration of the ammonia water is 25-30%, and the soaking time is 0.5-1h.
[0040] In some embodiments, in step S3, the drying temperature is 60-90°C.
[0041] The conductive structural color powder obtained in this application has high thermal stability. The reason is that the glucose particles on the prepared conductive structural color powder are distributed more evenly, making the stress distribution of the material more uniform when heated. At the same time, the temperature of the preparation process is high, which improves the thermal stability of the powder. The specific reasons are analyzed as follows; 1. In-situ growth technology: Through the in-situ growth of glucose, the interaction between the conductive powder and the glucose solution is closer. This growth method helps to form a stable structure, thereby improving the thermal stability of the material.
[0042] 2. Glucose heat treatment: Glucose will undergo a chemical reaction under hydrothermal conditions to form carbon microspheres. The nano-carbon spheres prepared by the glucose hydrothermal method are green, environmentally friendly and pollution-free. At the same time, no initiators or toxic solvents are introduced during the experiment. The prepared carbon spheres have uniform particle size and controllable size, which helps to improve the thermal stability of the material.
[0043] 3. High temperature heat treatment: During the preparation process, the reactor is heated to 250°C and kept warm for 2 hours. Such high temperature heat treatment helps to form a stable carbon structure and enhance the thermal stability of the material.
[0044] 4. Post-treatment with ammonia solution: After the composite is immersed in ammonia solution, the structural stability of the material is further enhanced. Ammonia treatment may help improve the surface properties of the material and enhance its thermal stability.
[0045] 5. Drying process: Drying is carried out at a temperature of 80°C. This step helps to remove moisture and volatile substances in the material, reduce heat loss during heat treatment, and thus improve the thermal stability of the material.
[0046] This application uses steps such as glucose in situ growth technology, high-temperature heat treatment, and ammonia solution post-treatment to make the prepared conductive structural color powder exhibit excellent thermal stability, so that the obtained material can still maintain its structure and performance in a high temperature environment and is suitable for various high-temperature application scenarios.
[0047] The present application provides an application of conductive structural color powder based on in-situ growth of glucose in color regulation.
[0048] The present solution is further described below through specific embodiments.
[0049] Example 1 A method for preparing conductive structural color powder based on in-situ growth of glucose, comprising the following steps: S1. 2 g of conductive powder (single-walled carbon nanotubes) was placed in a solution of acetone, ethanol and deionized water in a volume ratio of 1:1:2 for pretreatment, and allowed to stand for 48 hours. The conductive powder was then taken out and placed in an oven to dry at 80°C to obtain pretreated conductive powder. S2. 4 g of glucose was dissolved in 16 ml of deionized water to obtain a glucose solution, and then the pretreated conductive powder was poured into the glucose solution to obtain a mixed solution, and then the mixed solution was subjected to ultrasonic dispersion treatment (50 Hz), and then transferred to a reactor, and the reactor was placed in a muffle furnace and heated to 250° C. at a heating rate of 3° C. / min, and the reactor was kept warm for 2 hours, and then the powder was taken out after the reactor was cooled to room temperature to obtain a composite; S3. The composite is soaked in an ammonia solution for 1 hour and then taken out, and then placed in an oven and dried at 80° C. to obtain a green powder with conductive ability, that is, a conductive structural color powder based on in-situ growth of glucose.
[0050] Example 2 A method for preparing conductive structural color powder based on in-situ growth of glucose, comprising the following steps: S1. 2 g of conductive powder (single-walled carbon nanotubes) was placed in a solution of acetone, ethanol and deionized water in a volume ratio of 1:1:2 for pretreatment, and allowed to stand for 48 hours. The conductive powder was then taken out and placed in an oven to dry at 80°C to obtain pretreated conductive powder. S2. 3 g of glucose was dissolved in 17 ml of deionized water to obtain a glucose solution, and then the pretreated conductive powder was poured into the glucose solution to obtain a mixed solution, and then the mixed solution was subjected to ultrasonic dispersion treatment (50 Hz), and then transferred to a reactor, and the reactor was placed in a muffle furnace and heated to 250°C at a heating rate of 3°C / min. After being kept warm for 2 hours, the powder was taken out after the reactor was cooled to room temperature to obtain a composite; S3. The composite was soaked in an ammonia solution for 1 hour and then taken out, and then placed in an oven and dried at 80° C. to obtain a purple powder with conductive ability, which is a conductive structural color powder based on in-situ growth of glucose.
[0051] Example 3 A method for preparing conductive structural color powder based on in-situ growth of glucose, comprising the following steps: S1. 2 g of conductive powder (single-walled carbon nanotubes) was placed in a solution of acetone, ethanol and deionized water in a volume ratio of 1:1:2 for pretreatment, and allowed to stand for 48 hours. The conductive powder was then taken out and placed in an oven to dry at 80°C to obtain pretreated conductive powder. S2. 2 g of glucose was dissolved in 18 ml of deionized water to obtain a glucose solution, and then the pretreated conductive powder was poured into the glucose solution to obtain a mixed solution, and then the mixed solution was subjected to ultrasonic dispersion treatment (50 Hz), and then transferred to a reactor, and the reactor was placed in a muffle furnace and heated to 250° C. at a heating rate of 3° C. / min. After being kept warm for 2 hours, the powder was taken out after the reactor was cooled to room temperature to obtain a composite; S3. The composite is soaked in an ammonia solution for 1 hour and then taken out, and then placed in an oven and dried at 80° C. to obtain a red powder with conductive ability, that is, a conductive structural color powder based on in-situ growth of glucose.
[0052] Example 4 A method for preparing conductive structural color powder based on in-situ growth of glucose, comprising the following steps: S1. 2 g of conductive powder (single-walled carbon nanotubes) was placed in a solution of acetone, ethanol and deionized water in a volume ratio of 1:1:2 for pretreatment, and allowed to stand for 48 hours. The conductive powder was then taken out and placed in an oven to dry at 80°C to obtain pretreated conductive powder. S2. 1 g of glucose was dissolved in 19 ml of deionized water to obtain a glucose solution, and then the pretreated conductive powder was poured into the glucose solution to obtain a mixed solution, and then the mixed solution was subjected to ultrasonic dispersion treatment (50 Hz), and then transferred to a reactor, and the reactor was placed in a muffle furnace and heated to 250° C. at a heating rate of 3° C. / min. After being kept warm for 2 hours, the powder was taken out after the reactor was cooled to room temperature to obtain a composite; S3. The composite is soaked in an ammonia solution for 1 hour and then taken out, and then placed in an oven and dried at 80° C. to obtain a yellow powder with conductive ability, that is, a conductive structural color powder based on in-situ growth of glucose.
[0053] Comparative Example 1 A method for preparing a conductive structural color powder based on in-situ growth of glucose, the other contents are exactly the same as those of Example 1, except that the concentration of the glucose solution is 0%.
[0054] Comparative Example 2 A method for preparing conductive structural color powder based on in-situ growth of glucose, the other contents are exactly the same as those of Example 1, except that glucose is replaced by fructose.
[0055] Comparative Example 3 The preparation method of the conductive structural color powder based on the in-situ growth of glucose is completely the same as that of Example 1 except that the conductive powder is replaced by silver powder.
[0056] Test and Evaluation Figure 1 Schematic diagram of the appearance of powders with different conductive structural colors; Under light conditions, the microsphere sizes of different conductive structural color powders are as follows Figure 2 As shown, the absorbance curves of different conductive structural color powders are as follows Figure 3 The reflection peak curves of the structural color powder at different angles are shown in Figure 5 shown.
[0057] Stability test: The conductive structural color powder was subjected to long-term (7 days) UV irradiation, water washing, acetic acid solution pickling and soaking to observe the color changes before and after soaking.
[0058] It can be seen from the test results that the conductive structural color powder prepared in the present application has uniform color, high color purity, obvious color contrast and good stability, is not easy to fade, and has low angle dependence.
[0059] Specifically, after ultraviolet irradiation, water washing, and acetic acid solution pickling and soaking, the color degree of the structural color powder obtained in the present application does not change much. This result may be attributed to the following key factors: 1. Light stability: The color of the structural color powder does not change much under ultraviolet irradiation, indicating that it has good light stability. This may be because the optical properties of the structural color powder mainly depend on the microscopic physical structure of the material rather than the chemical composition, so it has strong resistance to light radiation.
[0060] 2. Chemical stability: The color of the structural color powder remains stable after being pickled and soaked in acetic acid solution, showing its excellent chemical stability. This stability may be due to the carbon material formed by the glucose used in the powder at high temperature. This carbon material is generally highly chemically inert and not easy to react with other chemicals.
[0061] 3. Physical stability: The color of the structural color powder does not change much after washing in water, which indicates that its physical structure can remain stable under the action of water molecules. This stability may be related to the high refractive index characteristics of the carbon material in the powder, which has the potential to improve spatial resolution, thereby maintaining color uniformity and stability during the washing process.
[0062] 4. Color uniformity and angle independence: The color uniformity and angle independence of structural color powders may be related to the uniformity and order of their microstructure. Even close to the diffraction limit, structural color powders can still maintain different colors, which confirms the consistency of their colors at different viewing angles.
[0063] In summary, the reason why the structural color powder of the present application can maintain color stability after ultraviolet irradiation, water washing and acetic acid solution treatment is mainly due to its physical structure stability, chemical inertness and resistance to light radiation. These characteristics enable the structural color powder of the present application to maintain its color characteristics under various environmental conditions, showing excellent color stability and practicality.
[0064] like Figure 5 As shown, when the fixed angle of the reflection source is adjusted from 30° to 150°, the conductive structural color powder of the present application presents the same reflection peak, showing obvious structural color that is independent of the angle. This characteristic indicates that the developed color structure process can promote the stable color performance of the conductive structural color powder of the present application. After ultraviolet irradiation, water washing, and pickling and soaking in acetic acid solution, the color degree of the structural color powder obtained in the present application does not change much, which further confirms its excellent color stability. The following is a detailed explanation of this phenomenon: 1. Formation mechanism of structural color: The formation of structural color mainly depends on the periodic structure of photonic crystals, which can selectively reflect light of specific wavelengths to produce color. The generation of this color does not depend on pigments, but is achieved through optical effects such as light scattering, interference and diffraction. In the present invention, the composite formed by the reaction of conductive powder and glucose has a periodic microstructure, and these structures have consistent reflection characteristics for light at different angles, thereby achieving structural color that is independent of angle.
[0065] 2. Color stability: The color stability of structural color powders is due to their physical optical properties, which make the color unaffected by environmental factors such as ultraviolet irradiation, water washing and acid washing. These treatments do not change the periodic structure of photonic crystals, so the color remains stable. In addition, the high saturation and brightness of structural color powders are also one of the reasons why they have broad application prospects in the fields of display, decoration and anti-counterfeiting.
[0066] 3. Angle-independent color: The reflectance peaks of structural color powders remain consistent at different angles, indicating that their color performance is not affected by the viewing angle. This property is different from traditional pigment colors, which tend to change with changes in viewing angle. This angle independence of structural color gives it unique advantages in a variety of applications, especially in areas where color consistency is required.
[0067] 4. Effect of environmental factors on color: Even after treatments such as UV irradiation, water washing, and pickling with acetic acid solution, the color of the structural color powder did not change much, which proves its excellent weather resistance and chemical stability. This stability is crucial for long-term color retention in practical applications, especially in outdoor environments or products that require frequent cleaning.
[0068] In summary, the conductive structural color powder of the present application achieves color stability and angle independence through its unique photonic crystal structure, and these characteristics give it significant advantages in a variety of applications.
[0069] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A conductive structural color powder based on in-situ growth of glucose, characterized in that: The invention comprises conductive powder and glucose particles in-situ grown on the surface of the conductive powder. The conductive powder comprises one or more of multilayer graphene, single-walled carbon nanotube and carbon black.
2. The conductive structural color powder based on glucose in-situ growth according to claim 1, characterized in that: The particle size of the glucose particles on the conductive structural color powder is 260-350nm.
3. The conductive structural color powder based on glucose in-situ growth according to claim 1, characterized in that: The conductive structural color powder is spherical powder with the same particle size.
4. A method for preparing conductive structural color powder based on in-situ growth of glucose as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1. The conductive powder is placed in a water solvent for pretreatment, and then dried to obtain a pretreated conductive powder; S2. adding the pretreated conductive powder to a glucose solution, dispersing by ultrasonication, and heating the solution to obtain a composite; S3. Soaking the composite in an alkaline solution and then drying it to obtain the conductive structural color powder based on in-situ growth of glucose.
5. The preparation method according to claim 4, characterized in that: The concentration of the glucose solution is 0.1-20%.
6. The preparation method according to claim 4, characterized in that: The solvent in step S1 is water, and the pretreatment solution includes acetone, ethanol and deionized water in a volume ratio of 0.8-1:0.8-1:1.5-2; the standing time is 24-48 hours.
7. The preparation method according to claim 4, characterized in that: In step S2, the heating reaction process is: heating to 200-250°C at 2-5°C / min.
8. The preparation method according to claim 4, characterized in that: In step S3, the concentration of the ammonia water is 25-30%, and the soaking time is 0.5-1h.
9. The preparation method according to claim 4, characterized in that: In step S3, the drying temperature is 60-90°C.
10. Use of the conductive structural color powder based on in-situ growth of glucose as claimed in any one of claims 1 to 3 in color regulation.
Citation Information
Patent Citations
Preparation method of carbon nanotube-mesoporous carbon / sulfur composite material
CN111416109A
Two-dimensional transition metal carbide / conductive carbon fiber composite and preparation method and application thereof
CN111764155A
Toner for electrostatic latent image development
JP2018105971A